P196 WIR-center for sexual health and medicine: a care model to counter HIV/STI in germany. (14th July 2019) - Brockmeyer, Norbert; Schlüter, Christoph; Potthoff, Anja; Wach, Janet; Kayser, Arne; Schu, Martina; Jonas, Benjamin; Tossmann, Peter; Kasper, Andre; Skaletz-Rorowski, Adriane
Abstract : Background: Increasing incidence of sexually transmitted infections (STI) in Germany has shown the necessity of easily accessible sexual health services. Walk In Ruhr (WIR), a unique inter-institutional Center for Sexual Health and Medicine in Germany, unites the Outpatient Clinic, Public Health Department and four community-driven NGO. Together, they provide counseling, testing and treatment for different target groups (e.g. youth, MSM, swinger) in one building. Innovative methods in preventing HIV/STI [Online Partner Notification tool (PN), PrEP, Online Risk Test (ORT), HIV/STI-self-sampling-kit 'teST-It'] are developed and tested here. Health Advisers offer counseling, outreach-work and guidance to specialists. Methods: During a 21-month-evaluation-period, supported by the German Ministry of Health, clients completed a quantitative survey. Additional surveys, conducted independently by the WIR for PrEP- and 'teST-It'- users were included, the ORT, the PN usage and HIV/STI test diagnosis and treatment were analyzed. Results: The evaluation is ongoing. Until 2/2019 approx. 3.200 surveys will be completed. Initial results show that target groups differ regarding age, gender, sex-orientation, visit reason and WIR institutions they approach. Additional studies show that a quarter of the clients are HIV-positive. 10.5% of the clinic's patients and 10% of the Public Health Dept. clients were tested STI-positive. Treatment of C. trachomatis and N. gonorrhoeae was successful in 98% of all cases and in 93.5% of all M. genitalium cases. PrEP usage has been rising (144 new PrEP users since 10/2017) and the PN tool has been used 208 times since 06/2017. Since 12/2017, 4502 persons used the anonymous ORT. 'teST-It' is available since 09/2018. Conclusion: In contrast to common care concepts, WIR achieves high levels of recognition and acceptance among different target groups and the average population. The opportunity to access different organizations helps to meet the medical and counseling needs of the clients to reduce further transmission of HIV/STI. Disclosure: No significant relationships.